PEMETAAN KELURUSAN DAN APLIKASINYA UNTUK PENILAIAN BAHAYA GERAKAN TANAH: STUDI KASUS WILAYAH SUMEDANG - Nendi Rohaendi; Hilman Suwargana (PPSDM Geominerba, 2018)
Sumedang has a high potential for landslide. The landslide can cause property damages and casualties. According to some researches, landslide is affected by many factors, such as geological structure. One of the methods to discover the geological structure is by conducting lineament mapping based on SRTM data (shuttle radar topography mission). After the lineament mapping is collected, the fault density analysis is conducted by using geography information system software. Then, the result of the analysis is analyzed using qualitative methods of drainage pattern analysis, lithology, and rose diagram analysis. The result of the field check shows that the area with a high fault density has a high potential of landslide. The result of this research can be useful as a preliminary data for the comprehensive landslide analysis in the research area.